Determinan audit report lag dengan adopsi teknologi informasi sebagai moderasi pada bursa efek tiga negara - Nisa, Dilla Fadillatun; Widarsono, Agus; Widaningsih, Mimin (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to examine the factors that influence audit report lag, including auditor reputation, audit opinion, and audit tenure, with the moderating role of information technology adoption across stock exchanges in three countries: Indonesia, Malaysia, and Australia. Methods – This research uses a quantitative method with secondary data. The tool used for data processing and analysis is EViews 13, employing a panel data regression model. Findings - The results of the study reveal that: (1) Auditor reputation has a negative effect on audit report lag, (2) Audit opinion does not have a negative effect on audit report lag, (3) Audit tenure does not have a negative effect on audit report lag, (4) Information technology adoption does not moderate the effect of auditor reputation on audit report lag, (5) Information technology adoption does not moderate the effect of audit opinion on audit report lag, and (6) Information technology adoption does not moderate the effect of audit tenure on audit report lag. Implications - A This study reinforces agency theory by showing that auditor reputation can accelerate audit report lag. However, the insignificant findings of audit opinion and audit tenure suggest that traditional factors may not always apply in a cross-country context, thus audit theory should consider contextual factors and technological developments. Originality - The novelty of this research lies in the use of information technology adoption as a moderating variable and the comparative analysis across three countries.